TEKNIK ESTIMASI PARAMETER DAN KOMPONEN ERROR PADA DATA PANEL TIDAK LENGKAP DENGAN METODE FEASIBLE GENERALIZED LEAST SQUARE (FGLS) - Yayuk Setyaning Astutik (Unisda Journal of Mathematics and Computer Science (UJMC), 2018)
Unbalanced panel data classified in fixed effect and random effect with one-way and two-way. Dummy variable used to determine differences the intercept on the classification individual or time units with assuming the intercept varies between individuals and time, whereas the slope is constant. For the random effects, differences in characteristics individual and time accommodated on the error component model with unknown error covariance matrix. The method used for one-way is Feasible Generalized Least Square (FGLS). Modifications ANOVA by Wallace and Hussain used for variance component estimation on the error covariance matrix. Components Estimation of variance on the error covariance matrix using the OLS residuals as components of quadratic forms and equating to expectations. In this case study the factors that affect cash dividend represented by ROI, Cash Ratio, Current Ratio, Debt Total Assets, Earning Per Share, Debt Equity Ratio and Dividend Payout Ratio in the period 2012-2017 with 36 of consumer goods manufacturing company in IDX.